If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 91.2 = 8(m + 3.1) Reorder the terms: 91.2 = 8(3.1 + m) 91.2 = (3.1 * 8 + m * 8) 91.2 = (24.8 + 8m) Solving 91.2 = 24.8 + 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. 91.2 + -8m = 24.8 + 8m + -8m Combine like terms: 8m + -8m = 0 91.2 + -8m = 24.8 + 0 91.2 + -8m = 24.8 Add '-91.2' to each side of the equation. 91.2 + -91.2 + -8m = 24.8 + -91.2 Combine like terms: 91.2 + -91.2 = 0.0 0.0 + -8m = 24.8 + -91.2 -8m = 24.8 + -91.2 Combine like terms: 24.8 + -91.2 = -66.4 -8m = -66.4 Divide each side by '-8'. m = 8.3 Simplifying m = 8.3
| 5cx^2-5x+12=0 | | -36=-4n | | 9x-4x^3=9x+4 | | 42w^2+w-30=0 | | -4(6x+4)=8p-10 | | 170=-17k | | (X+1)(x+1)=-0.333333333 | | 3z+2=-2z-8 | | -3=1(x+7) | | 35=x-3+5(x-2) | | 4a+3(a-2)=8a-(6+a) | | 6-11=7x-12 | | y-(y+4)=y+8 | | 5=8x-7x+3 | | 6h-24=-6h+14 | | -68-2X+11X=76 | | 9x-4=8x-2 | | -6(7x-7)=42x-42 | | -10x=150 | | 6d-3d+3d-6=4d | | 112-(2y-1)=4 | | 12-5=3.75 | | 5p-(3+p)=6p+1 | | 4x+8=-1(x+3) | | 5c=-5 | | 10-21=-161 | | Y-12=5(x+7) | | 0=12x^2+2 | | 33(b-2)=4 | | 3x+11=77 | | 8n-13=67 | | (12x^2)+2=0 |